Efektivitas Micro-Intervention Mindfulness Untuk Mengurangi Perilaku Belanja Impulsif Online Pada Pekerja Muda Pengguna E-Commerce Aktif - Pindha Prameswary, Allviola Putri; Djudiah , Djudiah (Syntax Literate, 2026)
The rapid growth of e-commerce and instant payment systems has increased the tendency for online impulsive buying, particularly among young workers who are vulnerable to work-related stress and intensive digital promotions. This study aimed to examine the effectiveness of Micro-Intervention Mindfulness in reducing online impulsive buying behavior among young workers who actively use e-commerce platforms. A quantitative approach with a one-group pre-test–post-test design was employed. The participants consisted of six young workers aged 22–30 years who met the criteria of active e-commerce use and showed tendencies toward impulsive buying. The intervention was conducted through four sessions of micro-intervention mindfulness focusing on enhancing awareness and attention toward impulsive urges. Data were collected using the Impulse Buying Tendency Scale and analyzed using the Shapiro–Wilk normality test and paired sample t-test. The results revealed a significant difference between pretest and posttest scores (t = −14.861; p < 0.001), indicating a reduction in impulsive buying behavior after the intervention. These findings suggest that Micro-Intervention Mindfulness is effective in improving self-regulation and promoting more mindful and adaptive consumption behavior among young workers in the digital era.